DAMPAK PROGRAM ONE REGION ONE OFFTAKER TERHADAP PENDAPATAN PETANI PADI SAWAH (ORIZA SATIVA L.) DI KOTA SUKABUMI (Suatu kasus pada petani padi sawah Program One Region One Offtaker) - Sri Andayani; Euis Dasipah; Dety Sukmawati (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
To increase the income of rice farmers in Sukabumi City, the Sukabumi City Food Security, Agriculture and Fisheries Service made a new breakthrough, namely the One Roof program which began in 2020. This program was implemented as a farmer partner institution, in this program an offtaker was appointed who in terms of guarantees financing capital for farming and at the same time guaranteeing the market for agricultural products. Farmers will obtain a business financing loan facility from the offtaker with a guarantee that the resulting product is sold to the offtaker at a reasonable price. The existence of offtakers is expected to be able to reduce farmers' dependence on middlemen who generally harm farmers. In addition, there is assistance from sapras (fertilizers and pesticides) to alleviate the need for sapras whose prices are increasing. The purpose of this study was to analyze the differences in production costs, production and income of lowland rice farmers before and after participating in the One Roof program. The data analysis method used was unpaired t-test. The results of the analysis show that the cost of farming production before participating in the One Roof Program is Rp 8,178,302/Ha, and after Rp 7.723.236, this shows a significant difference. Rice production before joining the One Roof Program was 6,530 Kg/Ha, and after 6,542 Kg/Ha, showed no significant difference. For lowland rice farmers' income before and after participating in the One Roof program, it shows a significant difference, before Rp 17,941,762/Ha/MT, while after Rp 20,408,759/Ha/MT.